Development of a UHPLC-MS method to avoid the in-source dissociation interference in characterization of crocins from Buddlejae flos and its dyeing yellow rice - Cheng, Si; Mi, Jianing; Jiang, Shanshan; Li, Arong; Zhong, Zishao; Chen, Zhixia (Frontiers in Plant Science, 2025)
Buddlejae flos, the flower bud of Buddleja officinalis Maxim., has been used in traditional Chinese medicine to promote eye health and as a yellow food dye for cooking rice in China. Crocins are a class of essential pharmacological ingredients and edible pigments in Buddlejae flos. However, misidentification and inaccurate quantification often occur in ultra-high-performance liquid chromatography-mass spectrometry (UHPLC-MS) analysis of crocins in complex samples due to in-source dissociation and matrix effects. To avoid these interferences, we developed a UHPLC-MS approach by optimizing the chromatographic separation. In the present work, our approach facilitated the identification of crocin isomers that are usually masked by in-source dissociation species, expanding the number of detected crocins and derivatives to 28 in Buddlejae flos. Additionally, our strategy significantly enhanced the sensitivity of the UHPLC-MS method for detecting crocins in complex samples. Moreover, we performed UHPLC fingerprint analysis of 21 batches of Buddlejae flos to evaluate the geographical regionality of crocins biosynthesis. Furthermore, comparative quantification of crocins among Buddlejae flos, Gardenia fruit, and saffron reveals significant differences in the percentage of various types of crocins. The improved approach provides an informative and reliable profile of crocins in Buddlejae flos and yellow rice, which is promising for enhancing the quality control of Buddlejae flos and for potential utilization in the synthetic biology of crocins.